2011
DOI: 10.1523/jneurosci.5961-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

How Thalamus Connects to Spiny Stellate Cells in the Cat's Visual Cortex

Abstract: In the cat's visual cortex, the responses of simple cells seem to be totally determined by their thalamic input, yet only a few percent of the excitatory synapses in layer 4 arise from the thalamus. To resolve this discrepancy between structure and function, we used correlated light and electron microscopy to search individual spiny stellate cells (simple cells) for possible structural features that would explain the biophysical efficacy of the thalamic input, such as synaptic location on dendrites, size of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…Without staining these cell organelles, identification of synapses relies entirely on geometrical features, like the apposition of spines and boutons. da Costa and Martin (2011) have shown that geometrical features are not sufficient to identify synapses. In this paper we provide long range reconstructions with conventional osmium stained images, preserving all structural information for biological analysis of the data, such as synapse identification or automatic mitochondria reconstruction (Lucchi et al, 2012; Giuly et al, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…Without staining these cell organelles, identification of synapses relies entirely on geometrical features, like the apposition of spines and boutons. da Costa and Martin (2011) have shown that geometrical features are not sufficient to identify synapses. In this paper we provide long range reconstructions with conventional osmium stained images, preserving all structural information for biological analysis of the data, such as synapse identification or automatic mitochondria reconstruction (Lucchi et al, 2012; Giuly et al, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…Often, these approaches are combined with labeling the recorded neurons, allowing for reconstruction of the respective soma locations, dendrite morphologies and putative contact sites at light-microscopic levels (Feldmeyer et al, 1999, 2002; Sun et al, 2006; Frick et al, 2008; da Costa and Martin, 2011). Paired recording/reconstruction approaches are however limited to acute brain slices in vitro , where slice thicknesses of 300 μm result in substantial cutting of dendrites (Oberlaender et al, 2012a) and axons (Oberlaender et al, 2011), limiting these measurements to close-by neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Eight groups found evidence consistent with the predictions (McBride et al, 2008, Kleindienst et al, Makino and Malinow, 2011, Chen et al, 2012, Fu et al, 2012, Takahashi et al, 2012, Rah et al, 2013, Druckmann et al, 2014), while two groups did not (Jia et al, 2010, Chen et al, 2011, da Costa and Martin, 2011, Varga et al, 2011). This issue is not resolved and multiple interpretations are still valid (reviewed in DeBello et al, 2014).…”
Section: Discussionmentioning
confidence: 59%
“…Immunoelectron microscopy of representative contacts in owl ICX revealed true synapses made between tracer-labeled axons and the dendrites of CaMKII+ neurons (Rodriguez-Contreras et al, 2005). In a larger-scale study of thalamic synapses made onto layer 4 spiny stellate cells in cat visual cortex, contacts were identified at the LM level whenever a gap could not be discerned between axon and dendrite (da Costa and Martin, 2011). At the EM level, fully half of the false positives were found not to be in contact.…”
Section: Methodsmentioning
confidence: 99%